Meios de comunicação e interatividade com a TV digital: um estudo sobre suas possibilidades de uso no processo de ensino/aprendizagem - Santos, Paulo César dos (2010)
Communication means, if properly applied, can play an important role in Brazilian Education. Newspapers, radios, TVs, video players and computers have been used as teaching resources in schools for years. Since the invention of Digital Interactive TV (TVDI) new potentialities can be explored based on its interactivity within the educational context. Despite its potential to contribute in the teaching/learning process, teachers have faced a lot of difficulties to deal with it since the initial employment of that technology in school. This research investigates the use of these media and concentrates in the TV as a teaching tool by somewhat revoking the use of TV School and School Interactive and Digital TV (TVEDI). The current research was accomplished under methodological grounds of qualitative approach and descriptive purposes, by observing and analyzing some public schools that make use of such TVs. According to the researched data the outcome achieved from the use of both TVs was not satisfactory, due to problems, such as inadequate building framework, deficient maintenance support of the equipments, lack of qualified teachers and unclear purposes lined up according the pedagogical plans of the schools. Taking into consideration that those problems take place since the introduction of the Information and Communication Technologies (ICTs) in education, we believe that, if appropriate measures were not taken to solve those problems, they will also occur in the employment of TVDI for educational purposes as well as in the employment of any other technology to come